Graphic Contaminations: Cosmopolitics of the ‘I’ in American Born Chinese and Persepolis - Schumann, Claudia (Studier i Pædagogisk Filosofi, 2015)
The article explores the demands that the conflictual dimension of globalization poses for a cosmopolitan education. Such an emphasis seems necessary in times where the populations who undertake inter- and intra-national border crossings are increasingly those who are forced to: those trying to escape unbearable poverty, atrocious wars, the disenfranchised and victims of racist, sexist or religious persecution. Reflecting on the experiences articulated in the two graphic novels, Persepolis and American Born Chinese, the dimension of the globalizing world and its impact and demands on its future world citizens which comes to the fore is one that highlights the necessity for learning how to take a critical and political stance rather than the search for how education can facilitate a smooth adaptation to a new mobile order. Stanley Cavell’s examination of the relationship between autobiography, philosophy, and the founding of a self-reliant voice will be reconsidered in light of its contribution to re-thinking the meaning of a cosmopolitan education between critical self-appropriation and developing a transformative political vision of a new societal order.